Moyamoya disease with neuro-ophthalmic manifestations: a rare case report - Das, Dipankar (Eye Brain, 2010)
Moyamoya (meaning a hazy puff of smoke) disease (MMD) is a rare, idiopathic, persistent, occlusive cerebrovascular disease involving bilateral progressive stenosis or occlusion of a terminal portion of the internal carotid artery, or a proximal portion of the anterior cerebral arteries and the middle cerebral arteries. There are irregular perforating vascular networks (moyamoya vessels), seen in the base of the brain, which produce magnetic resonance images of this ‘puff of smoke’ condition. Although MMD is prevalent mostly in Japan, it is also occasionally seen outside Asia. We report an interesting case of bilateral optic nerve involvement of a radiologically diagnosed case of MMD in a young lady seen in the north-east part of India.